Tipos de processamento da dieta pré-inicial e seus efeitos sobre o desenvolvimento produtivo e saúde intestinal de frangos de corte - Pinto, Camila Alves (2017)
The aim of this study was to evaluate the impact of the type of processing of the preinitial diet on the productive performance and intestinal health of broilers. The work was carried out from 08/05/2016 to 07/30/2016. Eighteen (18) sheds of broiler production were used, with an average of 30,000 birds per shed, distributed in a completely randomized design in groups of two treatments (physical form of the diet) and nine replicates (shed), being, A - test group (pre-starter pelleted diet ); B - control group (pre-starter meal diet). Broilers were weighed on days 0, 04, 07, 14, 21, 28, 35, 42 and 49 days in the proportion of 2% of the total housed. The animal performance parameters such as Feed Conversion (FC), Final Weight (FW), Productive Efficiency Index (PEI), Daily Weight Gain (DWG), Mortality and Viability were evaluated.It was also evaluated the intestinal quality of the birds, in which 90 birds were submitted to necropsy at 28 days. The parameters analyzed for intestinal health evaluation were the presence of gizzard erosion, presence of cellular desquamation, excess mucus, thick intestine, fine intestine, altered intestinal tone and passage of food.The test group presented superior results to the control group for the variables, DWG, PEI, FW, mortality (P<0.05). In all evaluated periods, broilers fed a pre-starter pelleted diet presented greater daily weight gain than those fed a meal diet.The use of pelleted diet in the pre-starter phase resulted in a better productive performance throughout the breeding period, but did not interfere in the intestinal health of the broilers.